Stres kerja dan produktivitas kerja: peran kepuasan kerja sebagai variabel intervening - Deni Widyo Prasetyo (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2022)
The purpose of the study was to determine the effect of job stress on job satisfaction, the effect of job stress on work productivity, and to examine the role of job satisfaction as a mediating influence of work stress on productivity. Using primary data collected by questionnaire. The research population of employees of the production division of PT. Sejahtera Utama Bersama Jombang as many as 86 employees and all of them were taken as research samples. Data analysis for hypothesis testing in this study used path analysis (Path Analysis). The results showed that there was an effect of job stress on job satisfaction, there was an effect of job stress on employee work productivity. Job satisfaction does not mediate the effect of job stress on employee work productivity. The impact of work stress will be greater on the decline in work productivity than on job satisfaction. Companies are advised to provide activities that can reduce employee work stress such as family gathering activities, out bonds and so on.